Barriers for work in people with multiple sclerosis: a Norwegian cultural adaptation and validation of the short version of the multiple sclerosis work difficulties questionnaire - Normann, Britt; Arntzen, Ellen Christin; Honan, Cynthia A. (Frontiers in Rehabilitation Sciences, 2024)
Background and purposeMultiple sclerosis (MS) is associated with high rates of unemployment, and barriers for work are essential to identify in the regular follow-up of these people. The current study aimed to culturally adapt and evaluate the psychometric properties of the Norwegian version of the Multiple Sclerosis Work Difficulties Questionnaire-23 (MSWDQ-23).MethodsFollowing backward and forward translation, the Norwegian version of the MSWDQ-23 (MSWDQ-23NV) was completed by 229 people with multiple sclerosis (MS). Validity was evaluated through confirmatory factor analysis and by associating scores with employment status, disability, and health-related quality of life outcome measures. Convergent validity was checked by correlating MSWDQ-23 scores with alternative study measures. Internal consistencies were examined by Cronbach's alfa.ResultsA good fit for the data was demonstrated for the MSWDQ-23NV in confirmatory factor analysis, with excellent internal consistencies also demonstrated for the full scale and its subscales (physical barriers, psychological/cognitive barriers, external barriers). The MSWDQ-23NV subscales were related in the expected direction to health-related quality of life outcome measures. While higher scores on the physical barriers subscale was strongly associated with higher levels of disability and progressive MS types, higher scores on all subscales were associated with not working in the past year.DiscussionThe Norwegian MSWDQ-23 is an internally consistent and valid instrument to measure perceived work difficulties in persons with all types of MS in a Norwegian-speaking population. The MSWDQ-23NV can be considered a useful tool for health care professionals to assess self-reported work difficulties in persons with MS. The Norwegian MSWDQ-23 scale should be examined for test-retest reliability and considered implemented in the regular follow up at the MS-outpatient clinics in Norway to support employment maintenance.